From simulation to motor execution: a review of the impact of dynamic motor imagery on performance - Guillot, A.; Di Rienzo, F.; Frank, C.; Debarnot, U.; MacIntyre, T. E. (International Review of Sport and Exercise Psychology, 2024)
There is now ample evidence that motor imagery contributes to improve motor performance and promote motor learning and recovery. During the last decades, a large number of experimental studies and imagery frameworks were designed to determine the critical key components for effective imagery interventions. The extent to which athletes often move slightly during motor imagery has spawned specific interest in imagery research from a conceptual perspective, hence challenging the traditional idea that imagery requires to remain motionless. While a wealth of research has extensively decoupled motor imagery from action, more recent imagery theories specifically considered that athletes can perform a dynamic form of imagery, by adopting a congruent body position and embodying spatial and/or temporal features of the movement without entirely performing it. Spurred by the wide use of this form of imagery by athletes and the promising related experimental research, the present paper aims at reviewing the impact and predictive positive effects of dynamic motor imagery on motor performance. Direct implications for applied work, including specific instructions that dynamic motor imagery might have during different stages of the coaching process of athletes, are further considered. A framework for the appropriate timing for delivering dynamic imagery interventions is finally proposed.